Using CBA REACT Strategy Supported by Crossword Puzzle Game on the Topic of Acid-Base Titrations - Tuğçe Günter (Journal of Science Learning, 2023)
This research investigates the effect of the context-based approach (CBA) 'Relating-Experiencing-Applying- Cooperating- Transferring' (REACT) strategy supported with crossword puzzles on achieving the associate degree students in the chemistry laboratory course on the topic of acid-base titrations. A crossword puzzle game and four contexts related to daily life upon acid-base titrations were developed and applied within this context. This study is a pre-test post-test research design with a control group, and the study group consists of second-year students studying in the Vocational School of Health Services Medical Laboratory Techniques (MLT) (n = 65) and Pharmacy Services (PS) (n = 65) programs at Zonguldak in Turkey. The experimental group was taught the relevant topic by the CBA REACT strategy supported with a crossword puzzle game, whereas the control group was taught by the CBA REACT strategy. The study result showed that the experimental group students' sound and partial understandings and academic achievements were higher than the control group students.